2017
DOI: 10.3390/molecules22111908
|View full text |Cite
|
Sign up to set email alerts
|

Chitin and Cellulose Processing in Low-Temperature Electron Beam Plasma

Abstract: Polysaccharide processing by means of low-temperature Electron Beam Plasma (EBP) is a promising alternative to the time-consuming and environmentally hazardous chemical hydrolysis in oligosaccharide production. The present paper considers mechanisms of the EBP-stimulated destruction of crab shell chitin, cellulose sulfate, and microcrystalline cellulose, as well as characterization of the produced oligosaccharides. The polysaccharide powders were treated in oxygen EBP for 1–20 min at 40 °C in a mixing reactor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
(53 reference statements)
1
14
0
Order By: Relevance
“…There were several kinds of reactive ions, molecules, and free radicals, such as atomic oxygen (O), hydroxyl (OH), nitrogen molecule (N2), super oxide anion (O2−), and NO, in the plasma . It was reported that these reactive agents played an important role in the interaction between the plasma and cells .…”
Section: Discussionmentioning
confidence: 99%
“…There were several kinds of reactive ions, molecules, and free radicals, such as atomic oxygen (O), hydroxyl (OH), nitrogen molecule (N2), super oxide anion (O2−), and NO, in the plasma . It was reported that these reactive agents played an important role in the interaction between the plasma and cells .…”
Section: Discussionmentioning
confidence: 99%
“…Mass-spectrometer HALO 201-RC (Hiden Analytical, Warrington, UK) continuously monitored plasma generating medium composition. In particular, it could detect possible gaseous pollutants emitted by chitosan under the plasma treatment [42]: the total gas flow G1 + G2 must be sufficient to neglect these pollution exhausts. To prevent the plasma generating medium from pollution by residual air the working chamber was preliminary evacuated to a pressure of ~1 Pa after every reactor reloading and only then the chamber was filled with oxygen of spectroscopic grade (Scientific Industrial Center of National Research Center "Kurchatov Institute", Moscow, Russia), which was used in the most exper- Algorithms of the EB controller operation were preliminary optimized by numerical simulation of the EB propagation and absorption in aerosols.…”
Section: The Electron-beam Plasma Chemical Reactor For Chitosan Procementioning
confidence: 99%
“…IR spectral measurements in a wavenumber range 500-5000 cm −1 with a resolution of 4 cm −1 were carried out by a FT-IR spectrometer Perkin-Elmer Spectrum 100 (Perkin-Elmer, Waltham, MA, USA) as described in [37,42].…”
Section: Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…Further, the modifications only occur on the fiber surface up to 50–100 nm depth, and thus does not change the properties of the fiber matrix [ 11 , 12 , 13 ]. During plasma treatment, air molecules undergo excitation, ionization, or dissociation, resulting in new excited states, metastable states, free particles, active groups, and various low-temperature plasma active substances such as ions, electrons, and photons [ 14 , 15 ]. It provides abundant active particles and free radicals for chemical reactions.…”
Section: Introductionmentioning
confidence: 99%